PENGARUH CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA PERUSAHAAN - Al Hadis T. Al Hadis; Dedy Takdir Syaifuddin; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study examines the effect of corporate governance and ownership structure on the performance of companies listed on the Indonesia Stock Exchange.The study population of the companies listed on the Indonesia Stock Exchange collected 43 companies. The selection sample uses purposive sampling thus the study sample won 14 companies. Data in the study were analyzed using path analysis with the help of SmartPLS 2 software.The results of the study: 1) corporate governance proxied by the size of the board of commissioners and independent commissioners has a positive and significant effect on company performance which is proxied by ROA and ROE. 2) The ownership structure that is proxied by foreign ownership has positive and significant of company performance which is proxied by ROA and ROE.Keywords: corporate governance, ownership structure and company performance